How Army Officers Attending the Command and General Staff Officers Course Decide Whether or Not to Pursue a Master’s Degree: Factors that Impact Their Decision and Unexpected Themes that Emerged - Charles D. Vance (Adult Education Research Conference, 2014)
This qualitative case study explored how Army officers attending the Command and General Staff Officers Course (CGSOC) decided whether or not to attend graduate school. CGSC students were interviewed and their own narratives described how they made their decisions.